1997
DOI: 10.1002/(sici)1097-0290(19970220)53:4<351::aid-bit1>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Can conformational changes be responsible for solvent and excipient effects on the catalytic behavior of subtilisin Carlsberg in organic solvents?

Abstract: We developed an FTIR (Fourier transform infrared) methodology for quantitatively assessing the secondary structure of proteins suspended in nonaqueous media. This methodology was used to measure the percentages of α‐helices and β‐sheets of subtilisin Carlsberg, prepared under different conditions, placed in various organic solvents. The title question was addressed with respect to some instances of markedly influencing the subtilisin activity in organic solvents reported in the literature. It is concluded that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
92
0
4

Year Published

1997
1997
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 123 publications
(106 citation statements)
references
References 42 publications
10
92
0
4
Order By: Relevance
“…The resulting spectra from both these measurements were similar; with amide I band maxima~1655 cm À1 in agreement with the literature. [19] This indicates that spectral acquisition employing the DRIFT method has little influence on the measurement outcome. Having confidence in the technique, we proceeded to study DRIFT spectra of the same lyophilised SC preparation simply mixed with finely ground KBr.…”
Section: Diffuse Reflectance Infrared Fourier Transform Spectroscopymentioning
confidence: 99%
“…The resulting spectra from both these measurements were similar; with amide I band maxima~1655 cm À1 in agreement with the literature. [19] This indicates that spectral acquisition employing the DRIFT method has little influence on the measurement outcome. Having confidence in the technique, we proceeded to study DRIFT spectra of the same lyophilised SC preparation simply mixed with finely ground KBr.…”
Section: Diffuse Reflectance Infrared Fourier Transform Spectroscopymentioning
confidence: 99%
“…It might promote structural changes in the protein. The relatively limited study here suggests that any changes are quite small over the lower water activity range, consistent with the idea that the structure is quite rigid (Griebenow & Klibanov 1997 The dashed line shows the effect on catalytic activity. (Partridge et al (1998).…”
Section: How Does Hydration Promote Catalytic Activity?mentioning
confidence: 99%
“…Although the use of organic solvents in the formulation process deactivates biological activity of the encapsulated protein to a great extent, they are unavoidably required to prepare the protein encapsulated PLGA microspheres [20]. Klibanov and co-workers have shown that the conformation of solid proteins in organic solvents is kinetically trapped [21]. Thus, protein unfolding is extremely slow under these preparation conditions.…”
Section: Resultsmentioning
confidence: 99%